Time‐gated luminescence imaging of positively charged poly‐l‐lysine‐coated highly microporous silicon nanoparticles in living Hydra polyp. Issue 12 (16th September 2020) - Schiattarella, Chiara; Moretta, Rosalba; Defforge, Thomas; Gautier, Gaël; Della Ventura, Bartolomeo; Terracciano, Monica; Tortiglione, Claudia; Fardella, Federica; Maddalena, Pasqualino; De Stefano, Luca; Velotta, Raffaele; Rea, Ilaria
Abstract: The development of non‐toxic fluorescent agents alternative to heavy metal‐based semiconductor quantum dots represents a relevant topic in biomedical research and in particular in the bioimaging field. Herein, highly luminescent Si─H terminal microporous silicon nanoparticles with μs‐lived photoemission are chemically modified with a two step process and successfully used as label‐free probes for in vivo time‐gated luminescence imaging. In this context, Hydra vulgaris is used as model organism for in vivo study and validity assessment. The application of time gating allows to pursue an effective sorting of the signals, getting rid of the most common sources of noise that are fast‐decay tissue autofluorescence and excitation scattering within the tissue. Indeed, an enhancement by a factor ~ 20 in the image signal‐to‐noise ratio can be estimated. Abstract : Poly‐l ‐lysine‐coated, luminescent highly microporous silicon nanoparticles are herein characterized and successfully used as label‐free longer‐lived probes for in vivo time‐gated luminescence imaging using Hydra vulgaris as target. The uptake in living organism is promoted by the positive surface charge of the nanocomposite. The outcomes show that time gating allows to get rid of nonspecific tissue autofluorescence and leads to a ~ 20‐fold enhancement in the image signal‐to‐noise ratio.